Roles of Chinese Police Amidst the COVID-19 Pandemic - Jiang, Feng (Policing: A Journal of Policy and Practice, 2020)
This article provides an overview of frontier issues of policing in China by examining the roles of police during the pandemic. It starts with a short introduction to the challenges and overall performance of China in keeping social order in the context of coronavirus disease (COVID-19). Then, it outlines four major missions the Chinese police have pursued, each with a sketch of what has been done and how law enforcement officials have managed to achieve their goals. It follows with a further insight into their strategies in social control in connection with the latest reforms on policing. Finally, it concludes briefly with features of Chinese policing.